Relevance of Electronic Effects on the Yield of CO2 from Methanol Oxidation - Godoi, Denis Ricardo Martins de [UNESP]; Villullas, Hebe de Las Mercedes [UNESP] (Amer Chemical Soc, 2012)
The yields of products of methanol oxidation (HCHO, HCOOH, and CO2) were studied for carbon-supported PtRu nanoparticles having different amounts of alloyed and oxide phases. It is demonstrated that the increase in the Pt 5d-band vacancy enhances the production of CO2, which is not directly related with the catalytic activity for CO oxidation. Results prove the relevant role of oxides and, at the same time, shed some new light on mechanistic aspects of methanol oxidation on PtRu nanocatalysts. It is also demonstrated that extrapolating from the behavior of smooth surfaces to nanoparticle systems is not always valid.